2021
DOI: 10.3389/fpsyg.2021.713952
|View full text |Cite
|
Sign up to set email alerts
|

The Mediational Role of Desire for Cultural Tightness on Concern With COVID-19 and Perceived Self-Control

Abstract: When ecological threats are more severe or prevalent, societies are more likely to tighten their social norms and punishments. Moreover, when people follow clear and tight rules, they are more prone to regulate their behavior (i.e., self-control) in order to avoid punishment. Therefore, we examined the mediating role of people’s endorsement of cultural tightness (i.e., support and desire) on the relationship between concern with COVID-19 threat and personal self-control. Our hypothesis was tested through a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 24 publications
(55 reference statements)
3
24
0
Order By: Relevance
“…In the present study, we focus on whether people’s desired tightness may mediate the relationship between the perceived COVID-19 threat and emotional reactions to noncompliance with COVID-19 health-protective behaviors; we expect that the perceived COVID-19 threat may increase people’s desire for restrictions and sanctions where they reside, consistent with previous findings [ 7 , 11 , 12 ]; given that age-related differences were found in the perceived cost of COVID-19 infection and actual health risk [ 23 , 31 ], we also expect that participants’ age will moderate this relationship. Although research on COVID-19 has been very common since the start of the pandemic, to our knowledge this is the first attempt to study how socio-psychological variables can predict reactions to pandemic-specific non-compliance.…”
Section: The Present Researchsupporting
confidence: 79%
See 4 more Smart Citations
“…In the present study, we focus on whether people’s desired tightness may mediate the relationship between the perceived COVID-19 threat and emotional reactions to noncompliance with COVID-19 health-protective behaviors; we expect that the perceived COVID-19 threat may increase people’s desire for restrictions and sanctions where they reside, consistent with previous findings [ 7 , 11 , 12 ]; given that age-related differences were found in the perceived cost of COVID-19 infection and actual health risk [ 23 , 31 ], we also expect that participants’ age will moderate this relationship. Although research on COVID-19 has been very common since the start of the pandemic, to our knowledge this is the first attempt to study how socio-psychological variables can predict reactions to pandemic-specific non-compliance.…”
Section: The Present Researchsupporting
confidence: 79%
“…As mentioned, when societies face societal threats, tight rules and punishments for people who deviate from norms may help them to coordinate in order to survive [ 8 , 10 ]. Likewise, correlational and experimental findings [ 7 , 11 , 12 ] showed that threat also affects the desire that rules be stricter in the face of threat. This finding has been consistently shown by as a number of studies.…”
Section: Threat Tightness and Implicationsmentioning
confidence: 99%
See 3 more Smart Citations